Perancangan Sistem Pendukung Keputusan Penentuan Prioritas Produk Unggulan Daerah Menggunakan Metode VIKOR - Khoirul Umam; Varian Eva Sulastri; Tiara Andini; Dian Utami Sutiksno; Mesran Mesran (JURIKOM (Jurnal Riset Komputer), 2018)
Each region currently has excellent products. Competition in marketing the superior products contained in an area increasingly tight, along with the increasing industrial growth rate. This resulted in the industry must be more observant to formulate policy strategy. Decision-making to determine the priority of regional superior products in accordance with the needs and capabilities required an accurate and effective decision so as not to choose and minimize losses both in terms of cost and time. The VIKOR method is part of the concept of Multi-Attribute Decision Making (MADM), which requires normalization of the calculations. The use of VIKOR, in the application of decision support systems by an agency, simply chooses some products that will be an alternative selection and gives weight values on alternative comparisons and criteria, while the criteria are the target market, the availability of raw materials, turnover, labor, technology used , specifications, origin of raw materials, quantity of raw materials. Based on the observations made by the authors on Local Superior Product (PUD) in performing decision support system of determining the priority of the region's superior products. In this study, the authors try to develop a system that can process decision support system determination of superior product areas with the hope that results can be obtained maximally and satisfactorily. The results are expected so that the selection of superior products area run in an orderly and orderly by the system is done well.